Effects of thermal cycles on the mechanical response of pultruded GFRP profiles used in civil engineering applications - Sousa, J. (2014)
This paper presents a literature review and results of an experimental study about the effects of thermal cycles on the physical and mechanical properties of pultruded glass fibre reinforced polymer (GFRP) profiles used in civil engineering structural applications. The GFRP profiles used in this study present similar fibre architecture, differing only in their matrix nature: unsaturated polyester and vinylester. Small-scale coupons obtained from both types of GFRP profiles were exposed to a Mediterranean range of thermal variations (-5 °C to 40 °C) for up to 190 cycles in a dry condition. The effects of such exposure on the physical and mechanical response of the GFRP materials were assessed and compared using the following experimental techniques: (a) dynamic mechanical analyses (DMA) to assess the viscoelastic behaviour; (b) tensile, flexural and interlaminar shear tests, to evaluate the mechanical properties; and (c) scanning electron microscopy (SEM), to monitor the potential changes in the microstructure due to the degradation (if any) caused by the thermal cycles, as well as the possible changes into the main mechanisms of fracture. After exposure to thermal cycles, the viscoelastic behaviour of the GFRP profiles presented only slight changes, indicating no significant degradation, neither in the matrix structure nor at the fibre-matrix interphase. In terms of mechanical properties, both types of GFRP materials suffered slight changes regarding tensile and interlaminar shear properties. Flexural properties were more affected, particularly the flexural modulus, especially in the first cycles, as degradation tended to stabilize for increasing cycles. The GFRP profile made of vinylester resin presented better overall performance than the one made of polyester, especially regarding the tensile properties. SEM observations of the surfaces of fracture of mechanically tested pultruded specimens showed two main mechanisms of crack propagation: cohesive rupture (matrix cracking), where the crack propagates inside the matrix, and adhesive rupture (fibre-matrix debonding), where the crack propagates at the interface fibre-matrix. Degradation of the polyester matrix caused by the thermal cycles is evidenced by extensive matrix microcracking and increased fibre-matrix debonding. The vinylester matrix resists better to such degradation as fibre-matrix debonding occurs in less extent, and matrix microcracking is scarcely present.